Organic Public Engagement How Ecological Thinking Transforms Public Engagement with Science - Lerner, Adam S. (Springer International Publishing, 2018)
This book advances organic public engagement methods based on ecological thinking. The authors draw on rich multi-disciplinary literature in ecological thinking as well as research from public engagement with science events held over the past several years across the United States. Through this combination of ecology theory and case studies, this book provides both the conceptual foundations and the proven practical applications of public engagement grounded in ecological thinking. It offers engagement scholars an effective and efficient means of carrying out their missions, while simultaneously building a more ecologically valid method for studying actually existing publics. .